Measuring the quality of democracy in Ghana : a comparative assessment of studies conducted by Freedom House, the Economic Intelligence Unit, the Ibrahim Index and the African Peer Review Mechanism (between 2005 and 2010) - Miti, Katabaro (University of Pretoria, 2015)
Dissertation (MA)--University of Pretoria, 2014.